Investigating diet and physical activity in Malaysia: education and family history of diabetes relate to lower levels of physical activity - Tam, Cai Lian; Bonn, Gregory; Yeoh, Si Han; Wong, Chee Piau (Frontiers in Psychology, 2014)
The National Health and Morbidity Survey (NHMS, 2011), estimates that the number of Malaysian adults suffering from type 2 diabetes has increased from 8.3% to 31.2% since 1996. This study is a preliminary investigation of possible factors contributing to this epidemic. Knowledge of diabetes, health locus of control, diet and exercise habits, as well as family history, education level and other demographic factors to better understand the correlates of risky and healthy behaviours. This was done as part of a larger initiative to improve prevention efforts. Questionnaires were completed by 770 individuals from three Malaysian states: Selangor, Penang, and Terengganu. Findings showed that people with better health knowledge and those who have a family history of type 2 diabetes were more likely to have healthy diets. Also, health knowledge related to lower alcohol consumption. Participants with diabetic family members, however, also reported higher levels of stress. Counterintuitively, higher educational levels, higher internal locus of control, better health knowledge, as well as a family history of diabetes all correlated with lower levels of physical activity. Thus, it is suggested that, while increasing health knowledge will be important in addressing the type 2 diabetes epidemic in Malaysia, especially in relation to diet, other cultural factors, specifically norms related to exercise and physical activity, also need to be addressed if the spread of type 2 diabetes is to be addressed over the long term.